2021
DOI: 10.3390/membranes11050321
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of a Corn Fiber Arabinoxylan Extract and Formulation of Biodegradable Films for Food Packaging

Abstract: Corn fiber from the corn starch industry is a by-product produced in large quantity that is mainly used in animal feed formulations, though it is still rich in valuable components, such as arabinoxylans, with proven film-forming ability. During arabinoxylans’ recovery under alkaline extraction, a dark-colored biopolymer fraction is obtained. In this work, a purified arabinoxylan extract from corn fiber with an intense brownish color was decolorized using hydrogen peroxide as the decolorizing agent. Biodegradab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…The control film (sample 1, Table 4) was the thinnest and had the most homogeneous thickness. Comparing this sample to the arabinoxylan-based films found in the literature, Weng et al reported a similar result for a film with the same formulation as this work (101 ± 12 µm) [26], while Péroval et al reached a slightly lower value, 90.8 ± 6.6 µm, as their arabinoxylan film had some differences in composition when compared to the control film sample [24]. As stated before, the addition of oil (samples 2 to 5, Table 4) produced films with uneven thicknesses.…”
Section: Thicknesssupporting
confidence: 84%
See 3 more Smart Citations
“…The control film (sample 1, Table 4) was the thinnest and had the most homogeneous thickness. Comparing this sample to the arabinoxylan-based films found in the literature, Weng et al reported a similar result for a film with the same formulation as this work (101 ± 12 µm) [26], while Péroval et al reached a slightly lower value, 90.8 ± 6.6 µm, as their arabinoxylan film had some differences in composition when compared to the control film sample [24]. As stated before, the addition of oil (samples 2 to 5, Table 4) produced films with uneven thicknesses.…”
Section: Thicknesssupporting
confidence: 84%
“…The arabinoxylan films were prepared using the casting method and following the procedure from Weng et al [26] with slight alterations. The purified lyophilised extract was dissolved in distilled water (2% (w/v)) under stirring at 45 • C until complete dissolution.…”
Section: Preparation Of the Arabinoxylan Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially in food industry, it is mainly used for the disinfection of food packaging and food such as dairy products [3]. In addition, it can also decolorize the food fibres [4]. In the current dairy industry, the aseptic packaging of yogurt and pure milk must use food-grade hydrogen peroxide in the disinfection process to achieve this, which has largely promoted the vigorous development of food-grade hydrogen peroxide, and its application is becoming more and more widespread [5].…”
Section: Introductionmentioning
confidence: 99%